« Dis-moi quel est ton paysage préféré » : exemple du Parc naturel régional de la Brenne - Claire Blouin-Gourbilière (Projets de Paysage)
The landscape image symbolises the identity of a place. A large number of territories are perceived, more or less consciously, through emblematic and iconographic representations, associating one or several landscape elements of a geographic region. These territories build their touristic communication on these landscape representations, expressing their cultural identity. This is the case for the regional natural parc of Brenne, located in the centre of France. The image associated with the territory is the “étang” (lake) of Grande Brenne as well as characteristic landscape elements such as : “étang”, the tree and the bird. Does this touristic representation of the parc allow the inhabitants of the surrounding towns to recognize their cultural identity ? During summer 2010, a "landscape" photographic competition questionned the representations of this landscape and its associated practises.